USING DIRECT METHOD IN TEACHING READING COMPREHENSION - Yuliani, Sri; Astria, Henni (English Community Journal, 2020)
The objective of  this research was to find out whether or not it is effective to teach reading comprehension through direct method to the eighth grade students of the State Junior High School 44 of Palembang. This study used a quasi -experimental method where the way of this method compare of two groups namely the experimental group and control group. The differences between them were in experimental group given treatment by using direct method; meanwhile in the control group was not given treatment. The population of this study was all  the eighth grade students of the State Junior High School 44 of Palembang. There were nine classes or 332 students, and two classes or 74 students were taken as the sample of the study by using  purposive non random sampling. In collecting the data, the researcher gave the test. The number of questions are 20 items.  The test was given twice namely, pretest and posttest. The items of the test in the post-test were exactly the same as those in the pre-test. It was calculated by using SPSS 16.0.  From the result of the research, It  indicated that  the students’ average score of the post-test in experimental group was 80.81 and the students’ average score of post-test in control group was 72.84. The result of statistical analysis between experimental group and control group t-obtained should be higher than t-table (0.279). Furthermore the result of the students’ score in experimental group and control group (value t-obtained) were 4.462. Since the value of t-obtained was higher than t-table, so that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It can be concluded that teaching reading comprehension through direct method to the eighth grade students of the State Junior High School  44 of Palembang was  effective.